2014
DOI: 10.1177/1687814020959885
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study on the effect of tool geometry on tool wear and surface roughness in hard turning

Abstract: The main purpose of this study is to investigate the influence of tool geometry (cutting edge angle, rake angle, and inclination angle) and to optimize tool wear and surface roughness in hard turning of AISI 1055 (52HRC) hardened steel by using TiN coated mixed ceramic inserts. The results show that the inclination angle is the major factor affecting the tool wear and the surface roughness in hard turning. With the increase in negative rake and inclination angles, the tool wear decreases, and the surface rough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…48 It is frequently used to address real-world issues involving multi-factor interaction because its response prediction results can also approximate the true response surface and produce the optimum prediction effect. 49 Equation (4) illustrates how the second-order response surface approach expands the Taylor expansion for a single variable to multiple variables 50 :…”
Section: Establishment and Analysis Of Surface Roughness Prediction M...mentioning
confidence: 99%
“…48 It is frequently used to address real-world issues involving multi-factor interaction because its response prediction results can also approximate the true response surface and produce the optimum prediction effect. 49 Equation (4) illustrates how the second-order response surface approach expands the Taylor expansion for a single variable to multiple variables 50 :…”
Section: Establishment and Analysis Of Surface Roughness Prediction M...mentioning
confidence: 99%
“…During sharpening, students and teachers only assess sharpness visually and do not pay attention to the important geometric angles of the cutting tool. Incorrect tool geometry will increase vibration during cutting, accelerate tool wear, and result in rough surface finish (Duc et al, 2020) (Sonia et al, 2013). HSS cutting tool angles are formed by sharpening them with a tool grinder machine, and the angle measurements need to be ensured using measuring tools (Setyawan, 2011) (Sugeng, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Mane et al [5] also reported that the depth of cut does not influence on the control of surface roughness when turning steel. For their part, Duc et al [6] found that the inclination angle is the major factor affecting the tool wear and the surface roughness on hard turning and that there is an optimal inclination and rake angle that provides the best cutting condition. Besides, tool wear affects the evolution of surface roughness and, in addition, friction coefficient depends on the adhesion and surface integrity of the machined part.…”
Section: Introductionmentioning
confidence: 99%